Chromosome-scale genomes of commercially important mahoganies, Swietenia macrophylla and Khaya senegalensis - Sunil Kumar Sahu; Min Liu; Guanlong Wang; Yewen Chen; Ruirui Li; Dongming Fang; Durgesh Nandini Sahu; Weixue Mu; Jinpu Wei; Jie Liu; Yuxian Zhao; Shouzhou Zhang; et al. (Scientific Data, 2023)
Abstract Mahogany species (family Meliaceae) are highly valued for their aesthetic and durable wood. Despite their economic and ecological importance, genomic resources for mahogany species are limited, hindering genetic improvement and conservation efforts. Here we perform chromosome-scale genome assemblies of two commercially important mahogany species: Swietenia macrophylla and Khaya senegalensis. By combining 10X sequencing and Hi-C data, we assemble high-quality genomes of 274.49 Mb (S. macrophylla) and 406.50 Mb (K. senegalensis), with scaffold N50 lengths of 8.51 Mb and 7.85 Mb, respectively. A total of 99.38% and 98.05% of the assembled sequences are anchored to 28 pseudo-chromosomes in S. macrophylla and K. senegalensis, respectively. We predict 34,129 and 31,908 protein-coding genes in S. macrophylla and K. senegalensis, respectively, of which 97.44% and 98.49% are functionally annotated. The chromosome-scale genome assemblies of these mahogany species could serve as a vital genetic resource, especially in understanding the properties of non-model woody plants. These high-quality genomes could support the development of molecular markers for breeding programs, conservation efforts, and the sustainable management of these valuable forest resources.